Tumor Growth Rate to Predict the Outcome of Patients with Neuroendocrine Tumors: Performance and Sources of Variability - Dromain, Clarisse; Sundin, Anders; Najran, Pavan; Vidal Trueba, Hector; Dioguardi Burgio, Marco; Crona, Joakim; Opalinska, Marta; Carvalho, Luciana; Franca, Regis; Borg, Philip; Vietti Violi, Naik; Schaefer, Niklaus; et al. (Neuroendocrinology, 2021)
Introduction: Tumor growth rate (TGR), percentage of change in tumor volume/month, has been previously identified as an early radiological biomarker for treatment monitoring in neuroendocrine tumor (NET) patients. We assessed the performance and reproducibility of TGR at 3 months (TGR3m) as a predictor factor of progression-free survival (PFS), including the impact of imaging method and reader variability. Methods: Baseline and 3-month (±1 month) CT/MRI images from patients with advanced, grade 1-2 NETs were retrospectively reviewed by 2 readers. Influence of number of targets, tumor burden, and location of lesion on the performance of TGR3m to predict PFS was assessed by uni/multivariable Cox regression analysis. Agreement between readers was assessed by Lin's concordance coefficient (LCC) and kappa coefficient (KC). Results: A total of 790 lesions were measured in 222 patients. Median PFS was 22.9 months. On univariable analysis, number of lesions (
CRIS-Team Scopus Importer:2021-09-03
Keywords: Biomarkers; Neuroendocrine tumors; Prognosis; Reproducibility of results